Management in knowledge management affects the intellectual capital of higher education institutions in Ecuador (Docentes 2.0 Journal, 2020)
Management is undoubtedly one of the tasks that universities must attend with priority one of the knowledge management variables. In this context, the present study relates to the knowledge management variables in the administrative process in its management stage and the variable intellectual capital. The objective of this study was to determine how the direction of knowledge management affects intellectual capital in higher education institutions in zone 4 of Ecuador. The research is of a basic - longitudinal type, jointly using documentary, historical, cross-sectional and correlational exploration. The methodology used was the collection of information obtained through data matrices applied to the units of analysis investigated. The dimensions that most influence the knowledge management variable are direction and control, as for the variable intellectual capital, the dimension that most intervenes is human capital.
Keywords: Intellectual Capital; Management, Knowledge Management; Institution of Higher Education